Cyclopentadienyl titanium imido compounds and their ethylene polymerization capability: Control of molecular weight distributions by imido N-substituents - Owen, C; Bolton, P; Cowley, A; Mountford, P (2007)
Reaction of the previously reported Cp*Ti(NtBu)Cl(py) (1) with bulky ortfzo-substituted anilines ArNH2 afforded the corresponding aryl imido derivatives Cp*Ti(NAr)Cl(py) (Ar = 2,6-C 6H3iPr2 (2), 2,6-C6H 3Br2 (3), 2-C6H41Bu (4), and 2-C6H4iPr (5)). Reaction of 2 with B(C 6F5)3 in C6D6 or heating in vacuo at 200 °C afforded the imido-bridged dimer Cp* 2Ti2(μ-N-2,6-C6H3iPr2)2Cl2 (8). Activation of 1-5 with MAO gave moderately active catalyst systems for the polymerization of ethylene in contrast to the previously reported, highly active titanium imido systems Ti(Me2[9]aneN3)(NR)Cl2/MAO and Ti{HC(Me2pz)3}(NR)Cl2/MAO, which are isolobal and isoelectronic with 1-5. The Cp*-supported precatalyst productivities were sensitive to both the imido N-substituents and initial precatalyst/ cocatalyst concentrations. Depending upon the imido N-substituents and initial precatalyst/cocatalyst concentrations, polyethylene with unimodal (either rather low or very high molecular weight) or bimodal molecular weight distributions can be obtained. Excess AlMe3 suppresses catalyst productivity but does not affect the overall molecular weight distribution in the system evaluated (1/MAO). Both chain transfer to aluminum and β-hydrogen transfer appear to be active pathways for formation of the low molecular weight fractions of the polymers formed with 1-5/MAO. Under otherwise identical polymerization conditions the catalyst systems 2/MAO and 8/MAO had comparable productivities and gave polyethylene with very similar molecular weight and molecular weight distributions, suggesting a potential role for binuclear species in the catalyst systems 1-5/MAO. © 2007 American Chemical Society.